Atrial fibrillation ablation guided with electroanatomical mapping system: A one year follow up (Medical Journal of Indonesia, 2010)
Aim AF is the most common arrhythmia in clinical practice and associated with an increased long-term risk of stroke, heart failure, and all-cause mortality. Catheter ablation of AF is relatively new modality to convert AF to sinus rhythm. This study was aimed to elaborate efficacy of catheter ablation in mixed type of AF. Methods Thirty patients (age of 52 ± 8 yo) comprised of 19 paroxysmal and 11 chronic AF underwent radiofrequency catheter ablation guided by electroanatomical CARTO™ mapping system. We used step wise ablation approach with circumferential pulmonary vein isolation (PVI) as a cornerstone. Additional ablation comprised of roof line, mitral isthmus line, complex fractionated atrial electrogram (CFAE), septal line and coronary sinus ablation was done respectively if indicated. All patients were followed up to 1 year for AF recurrence. Results Circumferential PVI was successfully performed in all patients but one. Average follow up period was 11.5 months. More than 80% of all patients remain in sinus rhythm at the end of follow period which 62% of them were free from any anti-arrhythmic drug. No major complication in all patients series. Conclusion Radiofrequency ablation guided with electroanatomical mapping is effective and safe in mixed type of AF. (Med J Indones 2009;19:172-8)